2013
DOI: 10.1016/j.ramb.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in pregnant women and its relation with socio-demographic variables and quality of life

Abstract: The majority of pregnant women have UI, negatively affecting the quality of their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 26 publications
8
42
2
13
Order By: Relevance
“…A cross-sectional study of 495 women found that 71% reported UI in the last 4 weeks of pregnancy, and they rated this as having a severe impact on their quality of life 59. The current findings suggest that PFMT is an effective prevention strategy for prenatal and postnatal UI, similar to findings in non-pregnant women 60–62.…”
Section: Discussionsupporting
confidence: 75%
“…A cross-sectional study of 495 women found that 71% reported UI in the last 4 weeks of pregnancy, and they rated this as having a severe impact on their quality of life 59. The current findings suggest that PFMT is an effective prevention strategy for prenatal and postnatal UI, similar to findings in non-pregnant women 60–62.…”
Section: Discussionsupporting
confidence: 75%
“…The protective effect of cesarean delivery is consistent throughout the literature . In the present study, complaints of UI were observed more frequently in those who had ventouse and vaginal deliveries.…”
Section: Discussionsupporting
confidence: 91%
“…Stress urinary incontinence (SUI) during pregnancy causes negative effects on women's overall quality of life during pregnancy (1,2), as well as pelvic floor function after delivery (3). Given that the number of pregnant women in China is increasing rapidly under the government's "Two-Child Policy," it is of great importance to improve women's quality of life by preventing SUI during pregnancy and postpartum.…”
Section: Introductionmentioning
confidence: 99%